2016
DOI: 10.5935/abc.20160146
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Function in Patients with Breast Cancer After Treatment with Anthracyclines

Abstract: BackgroundAtrial electromechanical delay (EMD) is used to predict atrial fibrillation, measured by echocardiography.ObjectivesThe aim of this study was to assess atrial EMD and mechanical function after anthracycline-containing chemotherapy.MethodsFifty-three patients with breast cancer (48 ± 8 years old) who received 240 mg/m2of Adriamycin, 2400 mg/m2 of cyclophosphamide, and 960 mg/m2 of paclitaxel were included in this retrospective study, as were 42 healthy subjects (47 ± 9 years old). Echocardiographic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 20 publications
0
31
0
1
Order By: Relevance
“…This divergence in risk may be mediated by a higher risk of AF. Several studies have reported an association between AF and cancer (13), but there are fewer data specific to EBC (52,53). A study of patients admitted to a surgical ward reported 2% prevalence of AF in presurgery electrocardiograms for EBC patients vs 0.6% in control subjects admitted for noncancer surgery (52).…”
Section: Discussionmentioning
confidence: 99%
“…This divergence in risk may be mediated by a higher risk of AF. Several studies have reported an association between AF and cancer (13), but there are fewer data specific to EBC (52,53). A study of patients admitted to a surgical ward reported 2% prevalence of AF in presurgery electrocardiograms for EBC patients vs 0.6% in control subjects admitted for noncancer surgery (52).…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that minimal and pre-A LAVIs were significantly higher in the cancer patients with borderline statistical significance for maximal LAVI. Yaylali et al showed that maximal and pre-contraction LAVs were significantly higher in the patients after anthracycline therapy in comparison with the healthy controls [7]. Shi et al did not find any difference in 3DE LAVIs measured immediately after completion of anthracycline therapy in non-Hodgkin lymphoma patients and the controls [6].…”
Section: Discussionmentioning
confidence: 99%
“…Shi and Yaylali reported significantly reduced passive LAEF and increased active LAEF, which demonstrated impaired conduit LA function and elevated booster pump LA function in breast cancer and non-Hodgkin lymphoma patients treated with anthracyclines [6,7]. Both groups of authors used only volumetric evaluation of LA phasic function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growing interest in cardio-oncology (the field of cardiovascular disease in patients with cancer) 1,2,3 has been accompanied by concerns about an increased risk of developing atrial fibrillation (AF) following cancer diagnosis, 4,5,6,7,8,9,10,11,12,13,14,15 as well as a higher risk of cancer following the recognition of AF. 15,16,17,18,19,20 In fact, AF has been proposed as a marker of an occult malignant neoplasm.…”
Section: Introductionmentioning
confidence: 99%